Preparation of complex surface coatings based on electrospark computer integrated deposition system. Issue 2 (10th January 2020) - Wang, X.R.; Wang, Z.Q.; Lin, T.S.; He, P.; Wang, R.J.; Bao, M.Y.
Abstract : Purpose: Electrospark deposition (ESD) attracts special attention from scientists and engineers because of its unique advantages. However, the ESD process has been carried out by hand up to the present. This prevents ESD from preparing complex curve/surface coatings owing to manual operation characteristics. To meet the coating precise preparation requirements for a lot of parts with complex surface from various industrial fields, this paper aims to obtain a new automatic ESD equipment, process and preparation methodology for complex surface coatings. Design/methodology/approach: By designing a special deposition holder and re-programming programmable machine controller, an ESD power supply and a computer numerical control milling machine are integrated to obtain an electrospark-computer integrated deposition system (ES-CIDS). Then, based on the ES-CIDS, a new ESD process, named electrospark-computer numerical control deposition (ES-CNCD) is developed. Furthermore, complex surface coatings are depicted using non-uniform rational B-spline mathematical model and modeled in a special software developed via MATLAB. Finally, deposition programs for a complex coating are generated using golden section interpolation method, and transferred to and executed by the ES-CIDS to accomplish the preparation of the complex surface coating. Findings: This paper demonstrates that it is possible and feasible to prepare complex surface coatings via an automatic ESD process (namely, ES-CNCD) precisely. Research limitations/implications: This paper can make automatic ESD process get more attention from scientific researchers and engineers, and promote the research of the ES-CNCD process/equipment. Practical implications: The ES-CNCD process can be used in the manufacturing of complex surface coatings, and in the remanufacturing of complex shape parts. Social implications: The ES-CIDS/ES-CNCD can promote the development of related equipment and technology, and bring opportunities and employment to ESD industry. Originality/value: This work prepares complex surface coatings precisely for the first time using a new automatic ESD process (ES-CNCD), which has wide application prospects in various industries.